Preparation for retirement of Filipino elderly in a selected community in Quezon City - Ignacio, Anna Katrina R.; de Leon, Ma. Perlita E. (Quezon City College of Home Economics, University of the Philippines Diliman, 2014)
ABSTRACT This qualitative study focuses on retirement because it is a transitory stage from middle adulthood to late adulthood that affects the individual and his/her family in many ways and aspects. The goal was to describe the practices done for preparation, the stressors experienced upon retirement, and the coping strategies utilized to cope with those stressors. Data were gathered by interviewing Filipino retirees, ages 65-79 upon interview, about ageing and retirement. Analysis of the data showed that most of the preparation, stressors, and coping strategies revolve around finances, with post-retirement activities to prevent or alleviate withdrawal anxiety coming in second. In addition, all of the participants classify themselves as ones who are successfully ageing.
#aThesis (B.S. Family Life and Child Development)--University of the Philippines Diliman.
Keywords: Retirement -- Philippines; Retirees -- Philippines